Labour Productivity as Indicator of Regional Economy Efficiency - G. Yu. Gagarina; L. S. Arkhipova; D. A. Sizova (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
The interrelation of labour productivity and economic situation in regions of the Russian Federation is really acute in current conditions, when such destructive factors as sanctions, inflation, instability on global markets due to coronavirus epidemic take place. Therefore, the key goal of the research is to estimate labour productivity in regions as a factor of economy efficiency. Among methods of research it is possible to mention comparative analysis of the indicator, typology of regions by a number of parameters in order to identify regional differentiation. It is assumed that the highest labour productivity is typical of raw-materials regions, which specialize on extraction and export of mineral resources. However, we should take into account that natural and climatic factors in this group of regions increase labour costs and therefore, cut labour productivity. The authors show that in regions with conventional specialization on manufacturing industry (when the raw-materials sector retains a certain importance) the said indicator demonstrates a high value, even in spite of some unfavorable trends on labour market. The authors used the following materials and research findings for preparing the article: results of deep interviews of employment service workers in the Ryazan region conducted in 2021 within the frames of the research ‘Digitalization of Labour Market and Employment in Russia: Trends and Mechanisms of Development’; materials of expert discussions and surveys of employment service heads in regions of the Central Federal District within the frames of the research ‘Organizational and Finance Mechanisms to Support Population Employment in 2021-2023, which Aims at Unemployment Reduction’